Helping substance-abusing women of vulnerable populations: effective treatment principles and strategies - Sun, An-Pyng (Columbia University Press, 2009)
Introduction : history, epidemiology, and consequences -- Etiologies and risk factors -- Factors in successful treatment programs for women -- Treatment methods -- Pregnant women -- Adolescent girls -- Older women -- Homeless women -- Street prostitutes -- Lesbians